Preliminary analysis of the presence of metals and metalloids in cigarette butts and fibers discarded on a tourist beach in Cartagena, Colombia (2024)
Cigarette butts are classified as plastic waste due to their composition of cellulose acetate fibers and are commonly found in beach sand. Their persistence in the environment, low biodegradability, and potential to interact with metals and metalloids during the aging process make them a significant subject of interest for research on coastal marine ecosystems. The aim of this study is to investigate the presence of metals such as hexavalent chromium Cr (VI), cadmium (Cd), and the metalloid arsenic (As) in cigarette butts (CBs), cigarette butt fibers (CBFs), and sand on a tourist beach in Cartagena, Colombia. The goal is to establish a baseline for potential contamination on the beach due to these elements. The methodology includes collecting samples of CBs, CBFs, and sand from different beach usage zones (active, rest, and service) and conducting standardized laboratory tests using atomic absorption spectroscopy for As and Cd and the standard colorimetric method for Cr (VI). The main findings indicate that arsenic levels reached 7.69, 5.75, and 3.47 mg As/kg in the sand, CBs, and CBFs, respectively. Cadmium and hexavalent chromium were found to be below the detection limit for the applied methodology. Additionally, mercury was detected at a concentration of 0.37 mg Hg/L in CBFs in the active zone in October.